How Do Social Contribution Value and Ownership Structure Influence Corporate Sustainable Growth in State-Owned Companies in Indonesia? - Kenny Ardillah (Journal of Accounting and Strategic Finance, 2021)
This study aims to prove empirically social contribution value, ownership concentration, and ownership circulation have a positive influence on corporate sustainable growth which is controlled by leverage and profitability. This study theory focuses on agency theory and stakeholder theory. The study sample focuses on state-owned companies listed on the Indonesia Stock Exchange in the 2014-2019 period. The data of this study’s sample used certain selection criteria with the use of the purposive sampling method to obtain 83 data that became the study sample. Data were analyzed using the multiple regression analysis methods. The results of this study indicate that social contribution value doesn’t influence corporate sustainable growth which is controlled by leverage and profitability. Ownership concentration and ownership circulation don’t influence corporate sustainable growth which is controlled by leverage and profitability. The social contribution value is a form of social and environmental responsibility for the company's operations towards stakeholders that don’t support the corporate sustainable growth of the company in the long term. The spread of the company’s share ownership structures that traded highly and weren’t concentrated on certain parties of shareholders can’t support the implementation of decisions made by management to increase the corporate sustainable growth. Because of its limitations, future studies can reflect the extent to which the assessment of corporate social contributions is carried out by one sector of a company other than state-owned companies.